Analisis Kopi Robusta Sidikalang Sebagai Pengahasil Kopi Terbaik Yang Mengalami Kenaikan Harga Jual - Juita Selfia Manullang; Gea Ibelala (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
One of Indonesia's best coffee-producing regions is located in Sumatra. Sidikalang coffee is one of the best types of coffee produced in the region, which is important information for coffee enthusiasts. Sidikalang is located in Dairi Regency, North Sumatra, where this coffee is grown. The purpose of this research is to describe so that people understand how to maintain and improve the quality of their products. The research method used is a qualitative method by analyzing through journals, books, and scientific sources and also descriptive discourse directly through whatsApp video calls with Mrs. Nurhaini Pasaribu as a robusta coffee farmer in Gurutuha village, Sidikalang, Lae Parira sub-district, Dairi district.. Information regarding the recent increase in Sidikalang coffee prices was obtained from a legitimate source, namely the Regional Executive Board of the Indonesian Coffee Exporters Association (BPD AEKI) as of July 7, 2023, data shows that the price of robusta coffee beans reached around Rp35,000/kg, an increase from the previous price of around Rp30,000/kg two months ago. This price includes coffee both in bean form and after being ground into powder. So, the increase in the selling price of Sidikalang Robusta Coffee is due to its increasingly good quality. Moreover, today's millennial farmers are more painstaking in the selection of seeds, fertilizers, soil and so on. Indeed, before the increase in the price of Robusta Sidikalang coffee, there was a problem with the quality of the coffee.